2022
DOI: 10.3390/ijerph192316016
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assessment and Learning Motivation in the Second Victim Phenomenon

Abstract: Introduction: The experience of a second victim phenomenon after an event plays a significant role in health care providers’ well-being. Untreated; it may lead to severe harm to victims and their families; other patients; hospitals; and society due to impairment or even loss of highly specialised employees. In order to manage the phenomenon, lifelong learning is inevitable but depends on learning motivation to attend training. This motivation may be impaired by overconfidence effects (e.g., over-placement and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
2
6
2
Order By: Relevance
“…This may be due to the small sample size, reduction of the SIMS instrument or motivational factors to participate in the survey. This finding differs from most of our previous studies, except one study on dysphagia management, which also detected only two patterns (‘experts’ and ‘recruitables’ but not ‘unawares’), and one study on second victims 13 that only showed slight differences between the clusters.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This may be due to the small sample size, reduction of the SIMS instrument or motivational factors to participate in the survey. This finding differs from most of our previous studies, except one study on dysphagia management, which also detected only two patterns (‘experts’ and ‘recruitables’ but not ‘unawares’), and one study on second victims 13 that only showed slight differences between the clusters.…”
Section: Discussioncontrasting
confidence: 99%
“… 6 An additional effect is the in-group bias of the clinical tribalism phenomenon (the belief that the own group is superior to other groups). 7 In healthcare, our working group detected these effects in different settings concerning hand hygiene, 8–11 basic life support, 12 second victim management, 13 dysphagiology (under review), and point of care ultrasound (under review). Four of these studies revealed three different types of motivated learners: motivated, confident and competent ‘experts’, motivated but overconfident ‘recruitables’, and amotivated as well as overconfident ‘unawares’.…”
Section: Introductionmentioning
confidence: 99%
“…We could show a positive correlation between overestimation with extrinsic motivation but not with the other motivational patterns. Compared to previous research [21][22][23], this is the rst time we detected these linear correlations, possibly due to the homogeneity of the sample. Moreover, the different computation models of overplacement and overestimation in the current study as a relative difference between the assessment of one's and other's competencies and the assessment of one's own competencies and the actual test performance might have also contributed to signi cant linear correlations as opposed to our previous studies, in which we calculated overcon dence effects as the absolute differences.…”
Section: Key Resultscontrasting
confidence: 73%
“…Our findings of a high symptom count may be valid and comparable to that of Austrian pediatricians [16]. Alternatively, the neglect in self-diagnosis could be attributed to an overconfidence effect in SVP [49] or an unintended violation of one's self-perception. This is comparable to findings in PTSD, where patients may neglect the significance of the disease [50].…”
Section: "Subjective" and "Objective" Svpsupporting
confidence: 76%